“DOST” Model to Link and Support Drug Resistant TB Patients From Private Sector: An Experience From Delhi, India - Vatsyayan, Vindhya; Pattery, Theresa; Sayyad, Khasim; Williams, Jason; Pal, Arnab; Panibatla, Vikas; Khanna, Ashwani (Frontiers in Public Health, 2022)
1) Background: The National TB Elimination Programme (NTEP) has quite successfully involved the private sector for referral of presumptive drug-resistant TB (DR-TB) patients for molecular testing and referral for DR-TB management. There was a challenge as all the referred patients were not reaching the facilities. A ‘DOST’ intervention model was implemented to strengthen the patient care pathway. We conducted this study to describe the patient care cascade, the clinico-demographic characteristics of patients linked to the treatment and to estimate the mean turn-around time for drug-resistant TB care services. (2) Methods: It is a cross-sectional study conducted in New Delhi during the period July 2019-December 2020 under programmatic settings (3) Results: A total of 9,331 patients were subjected to the CB-NAAT test and 382 (4%) were found to be resistant for rifampicin and 231(76%) were initiated on treatment in the public sector under NTEP; (4) Conclusions: The DOST intervention model developed to link the DR-TB patients from the private sector to the public sector DR-TB centres is found to be efficient and effective.